PEMANFAATAN METODE MARKER BASED TRACKING PADA TEKNOLOGI AUGMENTED REALITY (AR) UNTUK RANCANG BANGUN APLIKASI TUNTUNAN SHOLAT PADA PLATFORM ANDROID - Fitriastuti, Fatsyahrina; Irsyadi, Hijrul (Informasi Interaktif, 2021)
Prayer is a compulsory worship for every Muslim. Therefore, from the earliest possible time the children should begin to be taught to pray so that later when they reach the compulsory age for praying, the children are ready. Various methods can be applied by parents and teachers to teach how to perform prayers with the correct prayer movements and readings. The rapid development of information and communication technology, both in terms of hardware and software, can be used as a tool to create learning media for prayer guidance. Among them is the android based augmented reality (AR) technology. AR or known as "augmented reality" is a new technology in the multimedia field. AR technology that can combine the real world with the virtual world, is interactive according to real time (real time), and takes the form of 3D animation. AR is a technology that is able to combine virtual objects in two dimensions (2D) or three dimensions (3D) into a real environment, then project these objects in real time. AR technology is broadly divided into two, namely marker based trackin and markerless. In this study, a marker based tracking method will be used and runs on an Android-based smartphone to build a learning media application for prayer and reading movement guidance aimed at children to make it more interesting. With the marker based tracking method on augmented reality technology, children will get a profile picture of prayer movements and their reading.Keywords: augmented reality, marker based tracking